Force generation by a propagating wave of supramolecular nanofibers - Kubota, Ryou; Tanaka, Motomu (Nature Communications, 2020)
The rational design of spatiotemporal patterns in artificial molecular systems remains at an early stage of development. Here, the authors design a reaction network to control the formation and degradation of nanofibers by orthogonal chemical stimuli and describe force generation by a propagating wave of supramolecular nanofibers.
Gesehen am 18.09.2020